2011
DOI: 10.3856/vol39-issue2-fulltext-15
|View full text |Cite
|
Sign up to set email alerts
|

Use of antioxidants on rainbow trout Oncorhynchus mykiss (Walbaum, 1792) sperm diluent: effects on motility and fertilizing capability

Abstract: ABSTRACT. The present investigation determined how different antioxidants incorporated into the sperm diluent for cold storage of semen affected sperm motility and spermatozoan fertility capabilities of the rainbow trout. For the evaluations, fresh semen (C) and semen that had been stored without diluents (T1) were used as control groups. The diluents were prepared using a base of UCT diluents (T2), adding grape polyphenol (0.1 g 100 mL -1 ) (T3), trolox C (0.1 g 100 mL -1 ) (T4), polyphenol (0.1 g 100 mL -1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
(27 reference statements)
2
24
1
1
Order By: Relevance
“…We used a haemocyter for sperm cell count, and the sample had approximately 11 × 10 −9 ± 2 cells by ml before dilution, similar to values from another study [24]. The samples show an activation time of 180 ± 10 s and decay at 50%, similar to results from a previous study [25]. The samples were agitated daily and aerated by injecting compressed oxygen to prevent mortality of the sperm cells (which are not motile for the entire conservation period) and preserved for 20 days for periodic experiments [26].…”
Section: Collection and Handling Of Semen Samplessupporting
confidence: 69%
See 2 more Smart Citations
“…We used a haemocyter for sperm cell count, and the sample had approximately 11 × 10 −9 ± 2 cells by ml before dilution, similar to values from another study [24]. The samples show an activation time of 180 ± 10 s and decay at 50%, similar to results from a previous study [25]. The samples were agitated daily and aerated by injecting compressed oxygen to prevent mortality of the sperm cells (which are not motile for the entire conservation period) and preserved for 20 days for periodic experiments [26].…”
Section: Collection and Handling Of Semen Samplessupporting
confidence: 69%
“…However, these programs are expensive and require specialized instruments, therefore, their use is limited. Salmon sperm cells can be activated under laboratory conditions; the duration of motility can be assessed to evaluate sperm cell quality, the observation of initial motility, and the loss of certain properties as sperm cells in the sample lose their motility [15] [25]. Measuring semen quality is crucial in order to use these cells more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their effectiveness in freshwater teleost fish was proved by Lahnsteiner (), Lahnsteiner et al . (), Lahnsteiner and Mansour () and Ubilla and Valdebenito ().…”
Section: Cryopreservation Protocolsmentioning
confidence: 99%
“…Antioxidant molecules, such as ascorbic acid (vitamin C), catalase, glutathione and cysteine, may reduce the impact of oxidative stress and thus improve quality of thawed sperm, which have been tested in vitro and in vivo, on human, bovine, ram, rabbit, horse and boar sperm (Chatterjee & Gagnon, ; Großfeld et al., ; Maxwell & Stojanov, ; Vernet, Aitken, & Drevet, ) with inconsistent results. Available data on fish are scarce (Lahnsteiner, Mansour, & Kunz, ; Martinez‐Paramoa et al., ; Ogretmen, Inanan, & Ozturk, ; Ubilla & Valdebenito, ). Our previous work demonstrated that cryopreservation resulted in significant osmotic and oxidative stress in common carp Cyprinus carpio spermatozoa (Li & Li et al., ).…”
Section: Introductionmentioning
confidence: 99%